Safety and efficacy of adjuvant Sotagliflozin therapy in patients with T1D - an update and systematic review and meta-analysis - Lei, Yunzhen; Yao, Shanshan; Wang, Zhenglong; Tu, Qianxian; Yuan, Zhengqiang; Jiang, Qianfeng (Frontiers in Endocrinology, 2025)
ObjectiveThis meta-analysis aims to assess the safety and efficacy of Sotagliflozin in patients with type 1 diabetes (T1D).MethodsData on target organ protection, blood glucose levels, blood pressure, weight, insulin usage, and adverse events (AEs) associated with Sotagliflozin in the treatment of T1D were collected from databases including PubMed, Scopus, Web of Science, Embase, and the Cochrane Library. The search period extended until February 21, 2024, and included studies were restricted to randomized controlled trials (RCTs) investigating Sotagliflozin for T1D. The meta-analysis was performed using Stata 14 and RevMan 5.4.ResultsA total of 12 randomized controlled trials were included in the analysis, with treatment durations ranging from 14 to 52 weeks. Sotagliflozin, when used in combination with insulin therapy, resulted in significant reductions in cardiovascular disease (CVD) risk (−6.38%; 95% CI: −7.63 to −5.1; P < 0.05) and end-stage kidney disease (ESKD) risk (−5.0%; 95% CI: −7.62 to −2.3; P < 0.05). Additionally, Sotagliflozin significantly reduced blood glucose, blood pressure, and body weight, with these effects showing dose- and duration-dependent trends. Regarding adverse effects, the combination of insulin and Sotagliflozin was associated with an increased incidence of genital infections (Sotagliflozin group: 8% vs. control: 2%) but a reduced risk of fractures (Sotagliflozin group: 1% vs. control: 2%). No statistically significant differences were observed between the two groups for other outcomes, including diabetic ketoacidosis (DKA), hypoglycemia, mortality, cancer, nausea, diarrhea, urinary tract infections, or liver and kidney function impairment.ConclusionIn T1D patients, Sotagliflozin adjunct therapy improves blood glycemia, stabilizes blood pressure, and reduces cardiovascular risk factors. It also shows potential in lowering fracture risk, but the risk of DKA requires further clinical validation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/#joinuppage, identifier CRD42023467427.